Synthesis, Spectral and Antibacterial Studies of Some Hg(II) Chelates of Azo Dyes derived from 4-Amino-2,3-Dimethyl-1-Phenyl Pyrazol-5-one - Mathew, George; Hari Kumaran Nair, M.L. (Asian Journal of Chemistry, 2016)
Eleven new complexes of three azo dyes, 2,3-dimethyl-1-phenyl-4-(2-hydroxy-5-methyl phenyl azo)pyrazol-5-one (CAAPH), 2,3-dimethyl-1-phenyl-4-(2-hydroxy-5-chlorophenylazo)pyrazol-5-one (CPAAPH) and 2,3-dimethyl-1-phenyl-4-(2-hydroxy-5-nitrophenylazo)pyrazol-5-one (NPAAPH, derived from 4-amino antipyrine having the compositions [Hg(LH)X2], [Hg(L'H)X2] or [Hg(L"H)X2] (LH = CAAPH, L'H = CPAAPH, L"H = NPAAPH and X = Cl, Br, I or NO3) have been synthesized and characterized by elemental analysis, magnetic moment and conductance measurement, IR and 1HNMR spectral studies. The ligand NPAAPH and one of its complexes have been screened for their antibacterial activity against gram-positive and gram-negative bacteria. The ligands behave as neutral bidentate chelating agents. The complexes are found to be monomeric and neutral with a tetrahedral geometry.